Time and Age Trends in Free Sugar Intake from Food Groups among Children and Adolescents between 1985 and 2016 - Perrar, Ines; Schadow, Alena M.; Schmitting, Sarah; Buyken, Anette; Alexy, Ute (Nutrients)
Trend analyses suggest that free sugar (FS) intake—while still exceeding 10%E—has decreased among German children and adolescents since 2005, yet that intakes may shift from sugars naturally occurring in foods to added sugars as children age. Thus, we analysed time and age trends in FS intake (%E) from food groups among 3–18 year-olds (1985–2016) using 10,761 3-day dietary records from 1312 DONALD participants (660 boys, 652 girls) by use of polynomial mixed-effects regression models. Among girls, FS from sugar & sweets decreased from 1985 to 2016 (linear trend p < 0.0001), but not among boys (p > 0.05). In the total sample, FS intake from juices increased until 2000 and decreased since 2005 (linear, quadratic trend p < 0.0001). FS from sugar sweetened beverages (SSB) decreased non-linearly from 1985 to 2016 (girls: linear, quadratic, cubic trend p < 0.0001; boys: linear, quadratic, cubic trend p < 0.02). Younger children consumed more FS from juices than older ones, who had a higher FS intake from SSB. FS intake from sugar & sweets increased until early adolescence and decreased afterwards. Since sugar & sweets represent the main source of FS intake and the source with the least pronounced decline in intake, public health measures should focus on these products.

Assessing causal links between metabolic traits, inflammation and schizophrenia: a univariable and multivariable, bidirectional Mendelian-randomization study - Lin, Bochao D; Alkema, Anne; Peters, Triinu; Zinkstok, Janneke; Libuda, Lars; Hebebrand, Johannes; Antel, Jochen; Hinney, Anke; Cahn, Wiepke; Adan, Roger; Luykx, Jurjen J (International Journal of Epidemiology)
Abstract Background Blood immunoreactive biomarkers, such as C-reactive protein (CRP), and metabolic abnormalities have been associated with schizophrenia. Studies comprehensively and bidirectionally probing possible causal links between such blood constituents and liability to schizophrenia are lacking. Methods To disentangle putative causal links between CRP blood levels and schizophrenia in both directions, we conducted multiple univariable Mendelian-randomization (MR) analyses, ranging from fixed-effect to inverse variance-weighted (IVW), weighted-median, MR Egger and generalized summary-data-based Mendelian-randomization (GSMR) models. To prioritize metabolic risk factors for schizophrenia, a novel multivariable approach was applied: multivariable Mendelian-randomization–Bayesian model averaging (MR-BMA). Results All forward univariable MR analyses consistently showed that CRP has a protective effect on schizophrenia, whereas reverse MR analyses consistently suggested absent causal effects of schizophrenia liability on CRP blood levels. Using MR-BMA, as the top protective factors for schizophrenia we prioritized leucine and as the prime risk-factor triglycerides in medium very-low-density lipoprotein (VLDL). The five best-performing MR-BMA models provided one additional risk factor: triglycerides in large VLDL; and two additional protective factors: citrate and lactate. Conclusions Our results add to a growing body of literature hinting at metabolic changes—in particular of triglycerides—independently of medication status in schizophrenia. We also highlight the absent effects of genetic liability to schizophrenia on CRP levels.

Effects of LC-PUFA supply via complementary food on infant development—a food based intervention (RCT) embedded in a total diet concept - Kalhoff, Hermann; Mesch, Christina M.; Stimming, Madlen; Israel, Andreas; Spitzer, Christoph; Beganovic, Latifa; Perez, Rocio Estella; Koletzko, Berthold; Warschburger, Petra; Kersting, Mathilde; Libuda, Lars (European Journal of Clinical Nutrition)

Verbraucherbildung als Bildung für Lebensführung - Schlegel-Matthies, Kirsten (Verbraucherbildung: Ein weiter Weg zum mündigen Verbraucher)

Haushaltsbezogene Bildung – quo vadis? Daseinsvorsorge und Lebensführung im Wandel - Schlegel-Matthies, Kirsten (Haushalt in Bildung & Forschung)
Der Beitrag geht der Frage nach, wie haushaltsbezogene Bildung als Ernährungs- und Verbraucherbildung umgesetzt werden kann, damit Jugendliche selbstbestimmt und verantwortlich ihre individuellen Vorstellungen von einem „guten“ und „gelingenden“ Leben umsetzen können. Die Auseinandersetzung mit dem Zusammenwirken von gesellschaftlicher Lebensweise, privater Lebensführung und individuellen Lebensstilen erweist sich dabei als bedeutsam.

Dietary Glycemic Index and Load and the Risk of Type 2 Diabetes: A Systematic Review and Updated Meta-Analyses of Prospective Cohort Studies - Livesey, Geoffrey; Taylor, Richard; Livesey, Helen F.; Buyken, Anette; Jenkins, David J. A.; Augustin, Livia S. A.; Sievenpiper, John L.; Barclay, Alan W.; Liu, Simin; Wolever, Thomas M. S.; Willett, Walter C.; Brighenti, Furio; et al. (Nutrients)
Published meta-analyses indicate significant but inconsistent incident type-2 diabetes (T2D)-dietary glycemic index (GI) and glycemic load (GL) risk ratios or risk relations (RR). It is now over a decade ago that a published meta-analysis used a predefined standard to identify valid studies. Considering valid studies only, and using random effects dose–response meta-analysis (DRM) while withdrawing spurious results (p < 0.05), we ascertained whether these relations would support nutrition guidance, specifically for an RR > 1.20 with a lower 95% confidence limit >1.10 across typical intakes (approximately 10th to 90th percentiles of population intakes). The combined T2D–GI RR was 1.27 (1.15–1.40) (p < 0.001, n = 10 studies) per 10 units GI, while that for the T2D–GL RR was 1.26 (1.15–1.37) (p < 0.001, n = 15) per 80 g/d GL in a 2000 kcal (8400 kJ) diet. The corresponding global DRM using restricted cubic splines were 1.87 (1.56–2.25) (p < 0.001, n = 10) and 1.89 (1.66–2.16) (p < 0.001, n = 15) from 47.6 to 76.1 units GI and 73 to 257 g/d GL in a 2000 kcal diet, respectively. In conclusion, among adults initially in good health, diets higher in GI or GL were robustly associated with incident T2D. Together with mechanistic and other data, this supports that consideration should be given to these dietary risk factors in nutrition advice. Concerning the public health relevance at the global level, our evidence indicates that GI and GL are substantial food markers predicting the development of T2D worldwide, for persons of European ancestry and of East Asian ancestry.

Dietary Glycemic Index and Load and the Risk of Type 2 Diabetes: Assessment of Causal Relations - Livesey, Geoffrey; Taylor, Richard; Livesey, Helen F.; Buyken, Anette; Jenkins, David J. A.; Augustin, Livia S. A.; Sievenpiper, John L.; Barclay, Alan W.; Liu, Simin; Wolever, Thomas M. S.; Willett, Walter C.; Brighenti, Furio; et al. (Nutrients)
While dietary factors are important modifiable risk factors for type 2 diabetes (T2D), the causal role of carbohydrate quality in nutrition remains controversial. Dietary glycemic index (GI) and glycemic load (GL) have been examined in relation to the risk of T2D in multiple prospective cohort studies. Previous meta-analyses indicate significant relations but consideration of causality has been minimal. Here, the results of our recent meta-analyses of prospective cohort studies of 4 to 26-y follow-up are interpreted in the context of the nine Bradford-Hill criteria for causality, that is: (1) Strength of Association, (2) Consistency, (3) Specificity, (4) Temporality, (5) Biological Gradient, (6) Plausibility, (7) Experimental evidence, (8) Analogy, and (9) Coherence. These criteria necessitated referral to a body of literature wider than prospective cohort studies alone, especially in criteria 6 to 9. In this analysis, all nine of the Hill’s criteria were met for GI and GL indicating that we can be confident of a role for GI and GL as causal factors contributing to incident T2D. In addition, neither dietary fiber nor cereal fiber nor wholegrain were found to be reliable or effective surrogate measures of GI or GL. Finally, our cost–benefit analysis suggests food and nutrition advice favors lower GI or GL and would produce significant potential cost savings in national healthcare budgets. The high confidence in causal associations for incident T2D is sufficient to consider inclusion of GI and GL in food and nutrient-based recommendations.

Developmental trajectories of body mass index from childhood into late adolescence and subsequent late adolescence–young adulthood cardiometabolic risk markers - Oluwagbemigun, Kolade; Buyken, Anette; Alexy, Ute; Schmid, Matthias; Herder, Christian; Nöthlings, Ute (Cardiovascular Diabetology)

Vitamin D and the Risk of Depression: A Causal Relationship? Findings from a Mendelian Randomization Study - Libuda, Lars; Laabs, Björn-Hergen; Ludwig, Christine; Bühlmeier, Judith; Antel, Jochen; Hinney, Anke; Naaresh, Roaa; Föcker, Manuel; Hebebrand, Johannes; König, Inke R.; Peters, Triinu (Nutrients)
While observational studies show an association between 25(OH)vitamin D concentrations and depressive symptoms, intervention studies, which examine the preventive effects of vitamin D supplementation on the development of depression, are lacking. To estimate the role of lowered 25(OH)vitamin D concentrations in the etiology of depressive disorders, we conducted a two-sample Mendelian randomization (MR) study on depression, i.e., “depressive symptoms” (DS, n = 161,460) and “broad depression” (BD, n = 113,769 cases and 208,811 controls). Six single nucleotide polymorphisms (SNPs), which were genome-wide significantly associated with 25(OH)vitamin D concentrations in 79,366 subjects from the SUNLIGHT genome-wide association study (GWAS), were used as an instrumental variable. None of the six SNPs was associated with DS or BD (all p > 0.05). MR analysis revealed no causal effects of 25(OH)vitamin D concentration, either on DS (inverse variance weighted (IVW); b = 0.025, SE = 0.038, p = 0.52) or on BD (IVW; b = 0.020, SE = 0.012, p = 0.10). Sensitivity analyses confirmed that 25(OH)vitamin D concentrations were not significantly associated with DS or BD. The findings from this MR study indicate no causal relationship between vitamin D concentrations and depressive symptoms, or broad depression. Conflicting findings from observational studies might have resulted from residual confounding or reverse causation.

Risk factors for a low weight gain in the early stage of adolescent anorexia nervosa inpatient treatment: findings from a pilot study - Knoll-Pientka, Nadja; Bühlmeier, Judith; Peters, Triinu; Albrecht, Muriel; Adams, Frederike; Wustrau, Katharina; Teufel, Martin; Hebebrand, Johannes; Föcker, Manuel; Libuda, Lars (Eating and Weight Disorders - Studies on Anorexia, Bulimia and Obesity)

Clinical Trials Required to Assess Potential Benefits and Side Effects of Treatment of Patients With Anorexia Nervosa With Recombinant Human Leptin - Hebebrand, Johannes; Milos, Gabriella; Wabitsch, Martin; Teufel, Martin; Führer, Dagmar; Bühlmeier, Judith; Libuda, Lars; Ludwig, Christine; Antel, Jochen (Frontiers in Psychology)

Habitual Fructose Intake Relates to Insulin Sensitivity and Fatty Liver Index in Recent-Onset Type 2 Diabetes Patients and Individuals without Diabetes. - Weber, KS; Simon, MC; Strassburger, K; Markgraf, DF; Buyken, Anette; Szendroedi, J; Müssig, K; Roden, M; Group, GDS (Nutrients)

Dietary carbohydrates: a review of international recommendations and the methods used to derive them. - Buyken, Anette; Mela, DJ; Dussort, P; Johnson, IT; Macdonald, IA; Stowell, JD; FJPH, Brouns (Eur J Clin Nutr)

Caring, Cooking, Cleaning – repräsentative Zeitverwendungsmuster von Eltern in Paarbeziehungen - Klünder, Nina; Meier-Gräwe, Uta (Journal of Family Research)
As a result of the increasing labor force participation of mothers, this article questions how twoparent households divide the housework activities of caring, cooking and cleaning. Therefore three types of couples with different labor force participations were formed: Dual-earner couples, couples with additional female income and malebreadwinner couples. The time use for the mentioned activities was examined with a secondary analysis based on the German representative time use surveys of 2012/2013 and 2001/2002. The analysis showed that fulltime mothers spent the lowest amount of time for caring, cooking and cleaning. However, unemployed mothers spent the most time for these activities. Within a decade – from 2001/2002 to 2012/2013 – all mothers have reduced their time spent on household activities. Meanwhile, all parents in 2012/2013 take noticeably more time for child care. Regardless of the mother’s labor force participation, mothers still spent more time for caring, cooking and cleaning, especially on weekdays. Additionally, the everyday housework is divided by gender. Only on weekends, couples with employed mothers shared the care-work almost egalitarian.
Zusammenfassung
Vor dem Hintergrund der steigenden Erwerbstätigkeit von Müttern geht dieser Beitrag der Frage nach, wie Eltern in Paarbeziehungen die Haushaltsbereiche Betreuung, Beköstigung sowie Wohnungs- und Wäschereinigung untereinander aufteilen. Dazu werden drei Paartypen mit unterschiedlichem Erwerbsumfang gebildet: Zweiverdiener- Paare, Paare mit weiblichem Zuverdienst sowie Paare mit männlichem Familienernährer. Deren Zeitverwendung für die genannten Tätigkeiten wird mithilfe der repräsentativen Zeitverwendungserhebung 2012/2013 und 2001/2002 sekundäranalytisch untersucht. Die Analyse zeigt, dass vollzeiterwerbstätige Mütter täglich am wenigsten Zeit für die drei genannten Arbeitsbereiche im Haushalt aufwenden, nicht erwerbstätige Mütter hingegen am meisten. Innerhalb einer Dekade – von 2001/2002 bis 2012/2013 – haben alle untersuchten Mütter ihre Zeitverwendung für hauswirtschaftliche Tätigkeitsfelder reduziert, zeitgleich nehmen sich Eltern 2012/2013 deutlich mehr Zeit für Betreuungsaufgaben. Unabhängig des Erwerbsumfangs der Mutter ist die Arbeit des Alltags nach wie vor, besonders werktags, weiblich konnotiert und somit geschlechtsdifferenzierend aufgeteilt. Nur am Wochenende zeigt sich in Paaren mit erwerbstätiger Mutter bei der Betreuung eine annährend egalitäre Arbeitsteilung.

Zwischen selbst Gekochtem, Thermomix und Schulverpflegung – Innenansichten der Ernährungsversorgung von Familien mit erwerbstätigen Eltern - Klünder, Nina (Hauswirtschaft und Wissenschaft)

Relation of dietary glycemic index, glycemic load, added sugar intake, or fiber intake to the development of body composition between ages 2 and 7 y - Buyken, Anette; Cheng, Guo; Günther, Anke LB; Liese, Angela D; Remer, Thomas; Karaolis-Danckert, Nadina (The American Journal of Clinical Nutrition)

Flavonoid intake from fruit and vegetables during adolescence is prospectively associated with a favourable risk factor profile for type 2 diabetes in early adulthood - Penczynski, Katharina J.; Herder, Christian; Krupp, Danika; Rienks, Johanna; Egert, Sarah; Wudy, Stefan A.; Roden, Michael; Remer, Thomas; Buyken, Anette (European Journal of Nutrition)

Effect of Dietary Sugar Intake on Biomarkers of Subclinical Inflammation: A Systematic Review and Meta-Analysis of Intervention Studies - Della Corte, Karen; Perrar, Ines; Penczynski, Katharina; Schwingshackl, Lukas; Herder, Christian; Buyken, Anette (Nutrients)

The relevance of restrained eating behavior for circadian eating patterns in adolescents - Koch, Stefanie A. J.; Alexy, Ute; Diederichs, Tanja; Buyken, Anette; Roßbach, Sarah (PLOS ONE)

Dietary Patterns in Primary School are of Prospective Relevance for the Development of Body Composition in Two German Pediatric Populations - Wolters, Maike; Joslowski, Gesa; Plachta-Danielzik, Sandra; Standl, Marie; Müller, Manfred; Ahrens, Wolfgang; Buyken, Anette (Nutrients)
This study performed comparative analyses in two pediatric cohorts to identify dietary patterns during primary school years and examined their relevance to body composition development. Nutritional and anthropometric data at the beginning of primary school and two or four years later were available from 298 and 372 participants of IDEFICS-Germany (Identification and prevention of Dietary-induced and lifestyle-induced health Effects In Children and infants Study) and the KOPS (Kiel Obesity Prevention Study) cohort, respectively. Principal component analyses (PCA) and reduced rank regression (RRR) were used to identify dietary patterns at baseline and patterns of change in food group intake during primary school years. RRR extracted patterns explaining variations in changes in body mass index (BMI), fat mass index (FMI), and waist-to-height-ratio (WtHR). Associations between pattern adherence and excess gain in BMI, FMI, or WtHR (>75th percentile) during primary school years were examined using logistic regression. Among PCA patterns, only a change towards a more Mediterranean food choice during primary school years were associated with a favorable body composition development in IDEFICS-Germany (p < 0.05). In KOPS, RRR patterns characterized by a frequent consumption of fast foods or starchy carbohydrate foods were consistently associated with an excess gain in BMI and WtHR (all p < 0.005). In IDEFICS-Germany, excess gain in BMI, FMI, and WtHR were predicted by a frequent consumption of nuts, meat, and pizza at baseline and a decrease in the consumption frequency of protein sources and snack carbohydrates during primary school years (all p < 0.01). The study confirms an adverse impact of fast food consumption on body composition during primary school years. Combinations of protein and carbohydrate sources deserve further investigation.

Network meta-analysis reaches nutrition research - Schwingshackl, Lukas; Buyken, Anette; Chaimani, Anna (European Journal of Nutrition)

Association between full breastfeeding, timing of complementary food introduction, and iron status in infancy in Germany: results of a secondary analysis of a randomized trial - Libuda, Lars; Hilbig, Annett; Berber-Al-Tawil, Seda; Kalhoff, Hermann; Kersting, Mathilde (European Journal of Nutrition)

The role of genetic variation of human metabolism for BMI, mental traits and mental disorders - Hebebrand, Johannes; Peters, Triinu; Schijven, Dick; Hebebrand, Moritz; Grasemann, Corinna; Winkler, Thomas W.; Heid, Iris M.; Antel, Jochen; Föcker, Manuel; Tegeler, Lisa; Brauner, Lena; Adan, Roger A.H.; et al. (Molecular Metabolism)

Effect of an vitamin D deficiency on depressive symptoms in child and adolescent psychiatric patients – a randomized controlled trial: study protocol - Föcker, Manuel; Antel, Jochen; Grasemann, Corinna; Führer, Dagmar; Timmesfeld, Nina; Öztürk, Dana; Peters, Triinu; Hinney, Anke; Hebebrand, Johannes; Libuda, Lars (BMC Psychiatry)

Peer Learning im Lehramtsstudium – Praxisbeispiel einer diversitysensiblen Lernbegleitung im Fach Hauswirtschaft - Hellweg, Joanna (Peer Learning an Hochschulen. Element einer diversitysensiblen, inklusiven Bildung)

Konsum, Ernährung und Gesundheit als zentrale Handlungsfelder für die alltägliche Lebensführung - Schlegel-Matthies, Kirsten (Haushalt in Bildung und Forschung (HiBiFo))
Der Artikel diskutiert zunächst Ziele, Aufgaben und Anforderungen an alltägliche Lebensführung und -gestaltung. Im Anschluss werden vor allem Wechselbeziehungen zwischen Entwicklungen und Strukturen in Wirtschaft, Gesellschaft und Politik einerseits und individueller Lebensführung andererseits betrachtet.

Das Lernzentrum Ernährung, Konsum, Gesundheit (LEKG) - Schlegel-Matthies, Kirsten; Hellweg, Joanna (Heterogenität als Chance. Bilanz und Perspektiven des Qualitätspakt Lehreprojekts an der Universität Paderborn)

„Keine Zeit!?“ – Über den Umgang mit einer kostbaren Ressource - Raacke, Georg (Alltägliche Lebensführung im Zusammenspiel von Individuum und Gesellschaft)
Zeit ist eine wichtige Ressource. Viele Menschen haben oft das Gefühl, die Zeit renne ihnen davon. Dabei ist Zeit auch immer eingebunden in gesellschaftliche Praxis. Während in der Vormoderne die Natur maßgeblich für die Bestimmung der Zeit war, brachte die Erfindung der Uhr ein völlig anderes Verständnis von Zeit und entsprechend von Zeithandeln. Zeit wurde nicht mehr als zyklisch verstanden, sondern als linearer Ablauf von Ereignissen. Heute gilt nicht mehr ausschließlich die Zeit der Uhr, Menschen sollen vielmehr flexibel ihre Zeit nutzen. Das hat nicht zuletzt eine unmittelbare Bedeutung für die alltägliche Lebensführung.

Polygene Formen der Adipositas und Störungs-übergreifende Analysen - Giuranna, J.; Antel, J.; Libuda, Lars; Reinehr, T.; Peters, T.; Hebebrand, J.; Hinney, A. (Adipositas - Ursachen, Folgeerkrankungen, Therapie)
Zusammenfassung Neben monogenen Formen und Hauptgen-Effekten sind für die genetische Prädisposition zur Adipositas polygene Mechanismen relevant. Meta-Analysen von genom-weiten Assoziationsstudien (GWAMA) haben mehr als 700 polygene Loci oder Polygene identifiziert, die genom-weit mit dem Body Mass index (BMI) assoziiert sind. Diese prädisponierenden Genvarianten (Allele) finden sich bei adipösen Probanden häufiger als bei normalgewichtigen oder schlanken Individuen. Mittels statistischer Analysen wurden diese Allele als Adipositas-Risikoallele klassifiziert. Jede einzelne polygene Variante leistet nur einen kleinen Beitrag zur Entwicklung einer Adipositas und erhöht das Gewicht pro Risikoallel nur um ca. hundert Gramm bis 1,5 Kilogramm. Der Erfolg der GWAMA hat in letzter Zeit Phänotyp übergreifende, sogenannte Cross- Disorder- und Cross-Phänotyp-Analysen, ermöglicht. Dabei können Risiko-Gene identifiziert werden, die mittels Analysen der einzelnen Erkrankungen / Phänotypen nicht entdeckt werden konnten. Funktionelle Studien (in vitro und in vivo) der GWAMA-abgeleiteten Polygene können zu einem besseren Verständnis der Mechanismen der Körpergewichtsregulation führen.

Trinken – was und wie viel? - Hilbig, A.; Libuda, Lars; Kalhoff, H. (Kinder- und Jugendmedizin)
Zusammenfassung Wasser ist für Menschen das wichtigste Nahrungsmittel. Die Verfügbarkeit von ausreichend Trinkwasser in hoher Qualität hat große Bedeutung und ist weltweit ein herausforderndes Entwicklungsziel. Wasser hat im Körper viele Funktionen, etwa als Baustoff, Reaktionsmedium und Reaktionspartner oder als wichtiges Transportmedium. Ein gut regulierter Wasserhaushalt ist Voraussetzung für normale Körperfunktionen und für langfristige Gesundheit. Eine Dehydratation kann zu Symptomen wie Schwäche, niedrigem Blutdruck und Hypotonie führen und die Bewusstseinslage beeinträchtigen. Ein vollständiger Wasserentzug ist schon nach Tagen tödlich. Aber auch eine leichte Dehydratation beeinträchtigt langfristig die körperliche und geistige Leistungsfähigkeit. Angaben zum täglichen Wasserbedarf stützen sich vornehmlich auf epidemiologisch ermittelte Zufuhrdaten, die für gesunde Kinder und Jugendliche adäquat sind. Im Durchschnitt sollten Schulkinder etwa einen Liter und Jugendliche etwa 1,5 Liter täglich trinken. Zuckergesüßte Getränke mit hoher Energiedichte könnten das Risiko für Übergewicht und Adipositas erhöhen. Ein gesunder Getränkeverzehr kann mit Maßnahmen zur Verhaltensund zur Verhältnisprävention gefördert werden.

Effects of breastfeeding on health outcomes in childhood: beyond dose-response relations - Buyken, Anette; Karaolis-Danckert, Nadina; Günther, Anke; Kersting, Mathilde (The American Journal of Clinical Nutrition)

Habitual Flavonoid Intake from Fruit and Vegetables during Adolescence and Serum Lipid Levels in Early Adulthood: A Prospective Analysis - Penczynski, Katharina; Remer, Thomas; Herder, Christian; Kalhoff, Hermann; Rienks, Johanna; Markgraf, Daniel; Roden, Michael; Buyken, Anette (Nutrients)

In adolescence a higher ‘eveningness in energy intake’ is associated with higher total daily energy intake - Diederichs, Tanja; Perrar, Ines; Roßbach, Sarah; Alexy, Ute; Buyken, Anette (Appetite)

Positive Effects of Practical Nutrition Lessons in a Primary SchoolSetting with a High Proportion of Migrant School Children - Weber, Katharina S.; Eitner, Jessica; Dauben, Laura; Spörkel, Olaf; Strassburger, Klaus; Sommer, Jörn; Kaiser, Barbara; Buyken, Anette; Kronsbein, Peter; Müssig, Karsten (Experimental and Clinical Endocrinology & Diabetes)
Abstract Background Children with migration background are at increased risk for overweight, partly due to less favorable dietary habits compared to their German counterparts. We examined the effects of practical nutrition lessons among children with a high proportion of migration background in a primary school setting. Methods Ten 3rd and 4th grade classes (n=166 children, 73% with migration background) received the intervention and nine school classes (n=139 children, 76% with migration background) served as control. Before, shortly after (only among the intervention group) and three months after the three-day practical nutrition lessons, the nutrition-related skills, behavior, attitudes, and knowledge of the children were assessed using a questionnaire. Changes between baseline and 1st follow-up among children of the intervention group were calculated using linear mixed models. Differences between the two groups for changes between baseline and 2nd follow-up were tested using linear regression analyses. Models were adjusted for potential confounders. Results Shortly after the practical nutrition lessons, the children of the intervention group had improved their knowledge (β=1.7; 95% CI: 1.0; 2.4, P<0.001) and skills (β=1.8; 95% CI: 1.4; 2.2, P<0.001). These changes were sustainable and larger in the intervention compared to the control group (knowledge: β=1.6; 95% CI: 0.7; 2.5, P<0.001; skills: β=1.3; 95% CI: 0.7; 1.9, P<0.001). Changes in nutrition-related behavior and attitudes did not differ between the groups. Conclusions Providing practical nutrition lessons in a primary school setting with a high proportion of children with immigrational background improved the children’s nutrition-related knowledge and skills.

Time and age trends in morning and evening protein intakes of German children and adolescents - Roßbach, Sarah; Diederichs, Tanja; Herder, Christian; Buyken, Anette; Alexy, Ute (Journal of Nutritional Science)
Abstract The present study describes time and age trends in morning and evening protein intakes and sources among German children and adolescents from 1985 to 2014. A total of 9757 three-day weighed dietary records of 1246 3- to 18-year-old participants of the Dortmund Nutritional and Anthropometric Longitudinally Designed (DONALD) study were analysed using polynomial mixed-effects regression models. Morning protein intake increased over the study period by approximately 1 % of morning energy intake (linear trend P < 0·0001), with the youngest and the oldest children having the highest protein intake (linear, quadratic trend P < 0·0001). Evening protein intake increased over time by approximately 2 % of evening energy intake in girls (linear trend P < 0·0001) and 1 % of evening energy intake in boys (quadratic trend P = 0·0313), with decreasing intake with age (girls: linear trend P < 0·0001; boys: linear trend P = 0·0963). Time trends were largely due to increases in protein from ‘starchy foods’. In conclusion, morning and evening protein intakes increased modestly between 1985 and 2014; these increases were, however, not accompanied by increases in traditional protein sources (i.e. meat or dairy products).

Dietary Acid Load and Mental Health Outcomes in Children and Adolescents: Results from the GINIplus and LISA Birth Cohort Studies - Bühlmeier, Judith; Harris, Carla; Koletzko, Sibylle; Lehmann, Irina; Bauer, Carl-Peter; Schikowski, Tamara; von Berg, Andrea; Berdel, Dietrich; Heinrich, Joachim; Hebebrand, Johannes; Föcker, Manuel; Standl, Marie; et al. (Nutrients)

Care und die Wissenschaft vom Haushalt

Association between habitual coffee consumption and metabolic syndrome in type 1 diabetes - Stutz, Bianca; Ahola, A.J.; Harjutsalo, V.; Forsblom, C.; Groop, P.-H. (Nutrition, Metabolism and Cardiovascular Diseases)
Keywords: Cardiology and Cardiovascular Medicine; Nutrition and Dietetics; Endocrinology; Diabetes and Metabolism; Medicine (miscellaneous)

Mahlzeitenmuster von Eltern in Paarbeziehungen - Klünder, Nina (Care und die Wissenschaft vom Haushalt)

Differenzierte Ermittlung des Gender Care Gap auf Basis der repräsentativen Zeitverwendungsdaten 2012/13 - Klünder, Nina

Essalltag und Arbeitsteilung von Eltern in Paarbeziehungen – Eine quantitative Analyse auf Basis der repräsentativen Zeitverwendungsdaten 2012/13 und 2001/02 - Klünder, Nina; Meier-Gräwe, Uta (Journal of Family Research)
The article examines the division of labor for everyday food routines of two-parent households depending on their labor force participation. Using data from the representative German Time Use Survey 2001/02 and 2012/13, three different pairs were formed: dual-earner couples, couples with additional female income and male-breadwinner couples Findings show that mother’s employment influences the time used for everyday food routines: It was found that the higher the employment rate of mothers, the less time was spent on food routine activities. Furthermore, the daily time used for everyday food routines was reduced from 2001/02 to 2012/13. The largest reductions were seen in the group of mothers working fulltime. Besides that, fathers were more engaged in meal preparation on the weekends, although the responsibility was the mother’s. In addition, the age and number of children in a household influenced the time used for everyday food routines. However, none of the examined pair constellations can help determine an egalitarian division of everyday food routines. There is still a labor division by gender.
Zusammenfassung
Der Beitrag untersucht die zeitliche Gestaltung sowie die innerfamiliale Arbeitsteilung des Essalltags von Müttern und Vätern in Paarbeziehungen differenziert nach deren Erwerbsumfang. Die Sekundäranalyse erfolgt auf Basis der repräsentativen Zeitverwendungsdaten 2012/13 und 2001/02, wobei drei Paarkonstellationen untersucht werden: Doppelverdiener-Paare, weibliche Zuverdiener- Paare sowie Paare mit männlichem Familienernährer. Die Analyse des Essalltags zeigt, dass der Erwerbsstatus der Mutter die zeitliche Gestaltung des Essalltags beeinflusst. Je höher dieser ist, desto weniger Zeit wird für die Ernährungsversorgung aufgewendet. Darüber hinaus hat sich die tägliche Zeitverwendung für die Ernährungsversorgung von 2001/02 bis 2012/13 reduziert, wobei die stärksten Einsparungen bei vollzeiterwerbstätigen Müttern zu konstatieren sind. Väter engagieren sich verstärkt am Wochenende bei der Mahlzeitenzubereitung, gleichwohl liegt die Verantwortung insgesamt bei den Müttern. Ebenso beeinflussen Alter und Anzahl der Kinder die Zeitverwendung für die Ernährungsversorgung. Letztlich kann in keiner untersuchten Paarkonstellation eine egalitäre Arbeitsteilung zur Gestaltung des Essalltags festgestellt werden. Vielmehr dominieren relativ ausgeprägte geschlechtsspezifische Arrangements.

Ausgewählte Ergebnisse der Zeitbudgeterhebungen 1991/92, 2001/02 und 2012/13 - Meier-Gräwe, Uta; Klünder, Nina (Familien stärken, Vielfalt ermöglichen. Bericht der familienpolitischen Kommission der Heinrich-Böll-Stiftung)

Generation Y. Wohin mit der Zeit? Ein empirischer Vergleich zur Zeitverwendung verschiedener Generationen - Zimmermann, Josepha; Klünder, Nina (Hauswirtschaft und Wissenschaft)

Carbohydrates from Sources with a Higher Glycemic Index during Adolescence: Is Evening Rather than Morning Intake Relevant for Risk Markers of Type 2 Diabetes in Young Adulthood? - Diederichs, Tanja; Herder, C; Roßbach, S; Roden, M; Wudy, SA; Nöthlings, U; Alexy, U; Buyken, Anette (Nutrients)

High protein intake along with paternal part-time employment is associated with higher body fat mass among girls from South China - Yang, Ming-zhe; Xue, Hong-mei; Pan, Jay; Libuda, Lars; Muckelbauer, Rebecca; Yang, Min; Quan, Liming; Cheng, Guo (European Journal of Nutrition)

Low 25(OH)-vitamin D concentrations are associated with emotional and behavioral problems in German children and adolescents - Husmann, Christiane; Frank, Mirjam; Schmidt, Börge; Jöckel, Karl-Heinz; Antel, Jochen; Reissner, Volker; Libuda, Lars; Hebebrand, Johannes; Föcker, Manuel (PLOS ONE)

Breastfeeding trends in healthy infants since 1990—results of the DONALD study - Libuda, Lars; Bolzenius, K; Alexy, U (European Journal of Clinical Nutrition)

Einzukaufen ist nicht schwer – Konsument zu sein dagegen sehr - Raacke, Georg (Haushalt in Bildung & Forschung)

„Wer früher stirbt, ist selbst schuld!“ – Ein kritischer Blick auf das aktuelle Gesundheitsregime - Raacke, Georg (Haushalt in Bildung & Forschung)

Vitamin D and mental health in children and adolescents - Föcker, Manuel; Antel, Jochen; Ring, Stefanie; Hahn, Denise; Kanal, Özlem; Öztürk, Dana; Hebebrand, Johannes; Libuda, Lars (European Child & Adolescent Psychiatry)